Esophageal stem cells and genetics/epigenetics in esophageal cancer - Croagh, D.; Frede, J.; Jones, P.; Kaur, Pritinder; Partensky, C.; Phillips, W. (New York Academy of Sciences, 2014)
© 2014 New York Academy of Sciences. The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the relationship between stem cells, cancer, and the esophagus; the behavior of esophageal stem cells; and the role of genetics and epigenetics in approaches to translational research.